2021
DOI: 10.3390/forecast3030028
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Electricity Price Forecasting by Employing Ensemble Empirical Mode Decomposition and Extreme Learning Machine

Abstract: Day-ahead electricity price forecasting plays a critical role in balancing energy consumption and generation, optimizing the decisions of electricity market participants, formulating energy trading strategies, and dispatching independent system operators. Despite the fact that much research on price forecasting has been published in recent years, it remains a difficult task because of the challenging nature of electricity prices that includes seasonality, sharp fluctuations in price, and high volatility. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Machine learning (ML)-based techniques are implemented in smart grids for providing mitigation and detection against cybersecurity attacks. The authors of [148] also implemented ML techniques to forecast electricity prices; however, we analyzed the ML techniques that are applied to detect the cyberattacks on smart meters that causes huge electricity cost. In Figure 7, we present the general framework adopted in smart grid.…”
Section: Deep Learning Based Cybersecurity Techniques In Smart Gridsmentioning
confidence: 99%
“…Machine learning (ML)-based techniques are implemented in smart grids for providing mitigation and detection against cybersecurity attacks. The authors of [148] also implemented ML techniques to forecast electricity prices; however, we analyzed the ML techniques that are applied to detect the cyberattacks on smart meters that causes huge electricity cost. In Figure 7, we present the general framework adopted in smart grid.…”
Section: Deep Learning Based Cybersecurity Techniques In Smart Gridsmentioning
confidence: 99%
“…This paper summarizes the formation of the electricity price in the spot market as follows [39][40][41][42][43]:…”
Section: Analysis On the Formation Mechanism Of Electricity Price In ...mentioning
confidence: 99%
“…Although this proposed method improved accuracy and efficiency compared to traditional methods, it failed to produce satisfactory mean absolute percentage error (MAPE) values. In another study [21], Ensemble Empirical Mode Decomposition was used in conjunction with various regression models such as Recurrent Neural Network (RNN), Multi-Layer Perceptron (MLP), SVR and ELM to obtain the actual predicted price of electricity based on data from the power systems of New South Wales (NSW), Queensland (QLD) and Victoria (VIC). According to the findings of this study, computational intelligence models produce a large MAPE; however, the suggested ELM model paired with the Ensemble Empirical Mode Decomposition manages to reduce the MAPE to less than 10%.…”
Section: Introductionmentioning
confidence: 99%